Ipertensione arteriosa polmonare: stima della casistica italiana e considerazioni sull’impatto sul budget dell’introduzione di tadalafil - Luca Guidi (Farmeconomia: Health Economics and Therapeutic Pathways, 2010)
This contribution is an attempt to estimate a range of Pulmonary Arterial Hypertension (PAH) prevalence in Italy using international literature and Italian drug market sales data and to evaluate the budget impact of the introduction of tadalafil among the actual drugs with specific indication for this pathology. The final epidemiological figure obtained shows a wide range of prevalence of PAH in Italy (900-3,000 cases). The introduction of tadalafil as PAH treatment should not cause a cost increase for the pharmaceutical budget considering that this new therapy will occupy essentially the patient segment actually treated with sildenafil and that it reduces, in a significant number of patients, the daily cost of PAH therapy through a stable, fixed dose, administration.